Neuronal coupling in the developing mammalian retina - Penn, AA (J Neurosci, 1994)
During the first 3 weeks of postnatal development in the ferret retina, cells in the ganglion cell layer spontaneously generate waves of electrical activity that travel across the retina in the absence of mature photoreceptors (Meister et al., 1991; Wong et al., 1993). Since few chemical synapses are present at the earliest stages when waves are present, we have explored whether gap junctions could act to correlate the activity of cells in the immature ganglion cell layer. Retinal ganglion cells in a living in vitro preparation from postnatal day 1 (P1) to P45 were intracellularly injected with the tracer Neurobiotin and the fluorescent dye Lucifer yellow, molecules that are known to pass through gap junctions. Lucifer yellow consistently filled only the injected cell, whereas Neurobiotin filled not only the injected cell but also passed to a constellation of neighboring cells. Coupling revealed by Neurobiotin is seen as early as P1, but, at this stage, it was not possible to identify the various morphological types of cells that were coupled. Thereafter, alpha ganglion cells showed homologous coupling to other alpha cells and to both conventionally placed and displaced amacrine cells. Likewise, gamma ganglion cells appeared coupled to other gamma cells and to amacrine cells. However, beta ganglion cells never showed tracer coupling in the neonatal or in adult retinas. The percentage of alpha and gamma cells that were coupled to other cells increased progressively with age. By the end of the third postnatal week, the pattern of Neurobiotin coupling in the ferret retina was adult-like, with virtually every injected alpha cell showing tracer coupling. Our observations suggest that intercellular junctions able to pass Neurobiotin are present in the inner plexiform layer during the period when the firing of retinal ganglion cells is highly correlated. Such junctions could contribute to synchronization of the activity of subsets of neighboring ganglion cells during development, but it cannot be the sole mediator of this activity because beta cells, which also participate in the correlated activity, showed no coupling at any stage. In addition, the continued presence of coupling in the adult retina implies that other changes in retinal circuitry are likely to contribute to the disappearance of the waves.